Design of stable inter-pillar spans at Tao Lekoa Mine - Dunn, Michael John (My University, 2008)
Since the commencement of mining at Tau Lekoa Mine in 1991, large geologically controlled falls of ground (FOG) have been problematic. Crush pillars are used to control these instabilities. Limiting of panel spans and cutting of pillars results in practical problems and production constraints which influence labour efficiencies, productivity and ultimately the economics of mining. This study analysed 81 large FOG that occurred over 1991 to 2001 using statistical methods. Statistical distributions describing the falls of ground, rock mass properties and mining parameters were determined. A probabilistic approach was used to evaluate stable spans and the crush pillar stability. The probability of large hanging wall instabilities was assessed for several mining situations using a Fault Tree methodology. Larger spans are possible provided an appropriate internal support system is designed. A probabilistic or risk based design approach is recommended as this is considered more logical than a deterministic approach.